Interventions to improve patient health education competence among nursing personnel: a scoping review protocol - Qirong Chen; Siyuan Tang; Ke Liu; Guiyun Wang; Shuyi Wang; Yanxia Qi (BMJ Open)
Introduction Patient health education has gradually become an indispensable and important part of nursing work. However, nursing personnel’s performance in this domain remains below satisfactory levels. The absence of patient health education competence (PHEC) constitutes a significant impediment to the effective implementation of such education by nursing personnel. Effective training in PHEC can enable nursing personnel to recognise the importance of patient health education, improve their attitudes towards patient health education and gain comprehensive knowledge and skills, thus improving patients’ health outcomes and quality of life, while also enhancing the overall quality of nursing. However, the related research is fragmented and there is a lack of systematic review of related literature. The scoping review aims to provide a comprehensive overview of the existing interventions related to cultivating the PHEC of nursing personnel.Methods and analysis We will use the Joanna Briggs Institute methodology to guide the scoping review proposed by this protocol. Between 1 April 2024 and 15 April 2024, a systematic search of electronic bibliographic databases, including Cochrane Library, PubMed, EMBASE, CINAHL, MEDLINE and ERIC, will be conducted. In addition, the grey literature source Google search engine will also be searched. Two reviewers will independently screen and conduct data extraction. Any discrepancies that arise will be resolved through consultation with a third reviewer. The data will be analysed and presented in tables, flow diagrams and text.Ethics and dissemination Ethical approval is not applicable for this study. We will share the findings from the study at national and/or international conferences and in a peer-reviewed journal in the fields of nursing education and/or patient education.Registration number This scoping review had been registered on Open Science Framework (http://osf.io/dapq7).